Pengaruh Kompensasi, Loyalitas, dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan PT. Mayora Indah Tbk Unit Jatake 1 Kota Tangerang - Ismia Ismia; Bambang Mardisentosa; Eko Trianto (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to analyze the effect of compensation, loyalty, and work discipline on employee productivity at PT. Mayora Indah Tbk Jatake 1 Unit, Tangerang City. The method used is quantitative with a causal approach. Data were collected through questionnaires that have been tested for validity and reliability, then processed using multiple linear regression analysis with the help of SPSS version 27. The results of the partial test showed that compensation had no significant effect on productivity (tcount = −1.452; sig. = 0.148), while loyalty (tcount = 5.521; sig. = 0.000) and work discipline (tcount = 3.286; sig. = 0.001) had a significant positive effect. Simultaneously, the three variables had a significant effect on productivity (F = 16.064; sig. = 0.000). The coefficient of determination (R²) of 0.225 indicates that compensation, loyalty, and discipline only explain 22.5% of the variation in productivity, while 77.5% is influenced by factors outside the research model. This finding confirms that increasing employee loyalty and discipline contributes more to productivity than compensation, so companies need to strengthen non-financial factors alongside compensation policies.